1996
DOI: 10.22201/igeof.00167169p.1996.35.4.535
|View full text |Cite
|
Sign up to set email alerts
|

A correlation between visual observations and instrumental records of cloudiness in Mexico

Abstract: En este trabajo se explora la utilidad climática de las observaciones visuales del estado del cielo a nivel medio mensual, mediante la búsqueda de relaciones estadísticas de alto nivel de ajuste con la heliofanía diaria media mensual medida con el heliógrafo Campbell-Stokes, para 56 puntos de México durante el periodo 1951-1980. Se muestra que el modelo estadístico obtenido para todos los puntos y todos los meses tiene un nivel de ajuste mayor que agrupando los datos por meses, por tipos de climas o por cintur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For example, Rangarajan et al (1984) calculated the SD values from 10-year mean cloud cover data using an empirical relationship with an accuracy of about 4-7 percent. Mean monthly SD for different latitudes was estimated with a RMSE% error in between 7% and 18% by Tejeda and Vargas (1996). Essa and Etman (2004) computed SD using cloud cover data for stations in Cairo, Bahtim and Sedi-Barrani in Egypt with the standard error of estimate (SEE) changing from 0.198 h to 0.844 h. El-Metwally (2005) proposed a nonlinear model which was based on cloud cover fraction and maximum and minimum temperatures to predict the relative SD for Egypt and it was shown that MBE% and RMSE% values changed from − 0.2% to -13.3% and from 2.3-14.5%, respectively.…”
mentioning
confidence: 99%
“…For example, Rangarajan et al (1984) calculated the SD values from 10-year mean cloud cover data using an empirical relationship with an accuracy of about 4-7 percent. Mean monthly SD for different latitudes was estimated with a RMSE% error in between 7% and 18% by Tejeda and Vargas (1996). Essa and Etman (2004) computed SD using cloud cover data for stations in Cairo, Bahtim and Sedi-Barrani in Egypt with the standard error of estimate (SEE) changing from 0.198 h to 0.844 h. El-Metwally (2005) proposed a nonlinear model which was based on cloud cover fraction and maximum and minimum temperatures to predict the relative SD for Egypt and it was shown that MBE% and RMSE% values changed from − 0.2% to -13.3% and from 2.3-14.5%, respectively.…”
mentioning
confidence: 99%